Felskian Phenomenopolitics: decolonial reading through postcritical singularities. Issue 6 (3rd June 2022) - Docherty, Michael
ABSTRACT: This essay intervenes in debates on the value of 'postcritique', countering concerns that the 'postcritical turn' represents a conservative abrogation of cultural inquiry's political responsibilities. I suggest that conventional critical forms reproduce in the relationship between reader and text a quasi-imperialist power dynamic, complicity in which is inescapable regardless of the reader's own political position, and that therefore postcritical approaches might in fact be of greatest political value and urgency in the treatment of literatures written from socio-politically marginal positions. I furnish this argument with a reading of Wilson Harris' Palace of the Peacock (1960). Taking cues from Rita Felski's invocation of phenomenology in her proposals for a postcritical practice, I deploy the work of Maurice Merleau-Ponty to demonstrate how Harris models stylistic and syntactic resistance to invasive forms of suspicious reading. Such resistance, I argue, constitutes a robustly political demand for the postcritical.